Instructing the method of ball shooting in the practice of young basketball players - Yakovykh, V. Yu.; Yakovykh, Yu. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the significance of ball-handling skills in the context of basketball and to explore the methods employed by coaches to teach these skills in early-stage training programs.